2017
DOI: 10.13189/fst.2017.050203
|View full text |Cite
|
Sign up to set email alerts
|

Production and Quality Evaluation of Flavoured Yoghurt from Graded Levels of Sweet Variety of African Bush Mango "Ugiri" (Irvingia gabonensis) Juice and Pulp

Abstract: Yoghurt was produced and flavoured with graded levels of African bush mango juice (ABMJ) and pulp (ABMP). African bush mango (Irvingia gabonensis) juice and pulp was used to substitute 0, 10, 20, 30, 40 and 50% of yoghurt. The chemical, sensory and microbiological properties of the yoghurts were determined using standard procedures. The results showed that the pH of the yoghurt ranged from 4.77 to 5.01. Plain yoghurt (PY) served as the control. The protein, ash, fat and fibre contents decreased with increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…The results showed that the protein content of some samples were found to be slightly lower than 2.70%. However, literature reviews have shown that the percentage of protein content of yoghurts samples have previously been reported in the range of 1.29-3.52% from other studies [20].…”
Section: Proximate Composition Of Yoghurt Samplesmentioning
confidence: 88%
“…The results showed that the protein content of some samples were found to be slightly lower than 2.70%. However, literature reviews have shown that the percentage of protein content of yoghurts samples have previously been reported in the range of 1.29-3.52% from other studies [20].…”
Section: Proximate Composition Of Yoghurt Samplesmentioning
confidence: 88%
“…Fat and protein contents decreased by the fortification of camel milk yogurt with persimmon pulp, ranging from 3.00% to 2.94% and 3.35% to 2.86%, respectively. Previous studies have shown that when the concentration of fruit pulp or juice increases in yogurt, a significant decrease in both protein content and fat percentage can be noticed; this decrease can be explained by the fact that fruit has a lower protein content compared to milk (Elsayed et al, 2020;Mbaeyi-Nwaoha et al, 2017).…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%